PROCESSES OF MASS-TRANSFER IN DENDRITE GRIT AT HARDENING OF STEEL INGOTS AND SLUGS - Ju. A. Samoilovich; V. I. Timoshpolskij; Е. V. Kalinevich (Литьë и металлургия, 2006)
The processes of mass transfer in dendritic grid of hardening steel ingots and continuously cast slugs are investigated using the mathematical modeling taking into account separation diffusion in two-phase zone and inflow of melt into the shrinkage zone. The regularities of the additives (by the example of carbon and sulfur) allocation are determined.